2010
DOI: 10.1177/0743558410391258
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-Racial Socialization Messages in the Identity Development of Second-Generation Haitians

Abstract: This study utilized qualitative inquiry to investigate the role of ethnic-racial socialization messages on ethnic and racial identity development among second-generation Haitians. Nine participants, ranging in age from 15 to 26, took part in individual semistructured qualitative interviews. The data were reviewed for emergent themes, as well as themes present in the ethnic-racial socialization and identity literature. Participants reported receiving positive messages (i.e., Cultural Socialization, Mainstream S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
(60 reference statements)
0
22
1
Order By: Relevance
“…However, the direction of the association between the promotion of mistrust and self-esteem was contrary to our hypotheses. Prior work has suggested that the promotion of mistrust constitutes a negative socialization message and encourages inter-ethnic hostility and other negative social and psychological outcomes (Caughy et al 2006;Huynh and Fuligni 2008;Joseph and Hunter 2011;Tran and Lee 2010). In fact, our data show that, at the bivariate level, the promotion of mistrust and preparation for bias messages indeed were associated with higher levels of depressive symptoms; however, these associations were not statistically significant in our final, prospective model.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…However, the direction of the association between the promotion of mistrust and self-esteem was contrary to our hypotheses. Prior work has suggested that the promotion of mistrust constitutes a negative socialization message and encourages inter-ethnic hostility and other negative social and psychological outcomes (Caughy et al 2006;Huynh and Fuligni 2008;Joseph and Hunter 2011;Tran and Lee 2010). In fact, our data show that, at the bivariate level, the promotion of mistrust and preparation for bias messages indeed were associated with higher levels of depressive symptoms; however, these associations were not statistically significant in our final, prospective model.…”
Section: Discussioncontrasting
confidence: 78%
“…Although less explored in the current literature, some recent research on second-generation Haitians suggests that negative socialization messages, such as the promotion of mistrust (i.e., messages that encourage adolescents to be wary of other ethnicities), might hinder ethnic identity exploration, thereby intentionally or inadvertently alienating individuals from their own ethnicities and subsequent identity development (Joseph and Hunter 2011). Research examining the links between the promotion of mistrust messages and identity development specifically among Asian-Americans has not yet been established; however, based on prior research with other groups, we generally expected that the promotion of mistrust would be negatively related to adolescents' ethnic identity development.…”
Section: Ethnic Socialization and Ethnic Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of risk, some studies found that preparation for bias directly predicted greater maladjustment such as higher depressive symptoms (e.g., Liu & Lau, ; Nelson et al, ), whereas other studies found that it exacerbated the negative effect of stressors on adjustment (e.g., Banerjee, Rowley, & Johnson, ; Dotterer & James, ). In contrast, other studies found preparation for bias to be promotive for youth either because it was directly associated with indicators of positive youth outcomes (e.g., D'hondt, Eccles, Van Houtte, & Stevens, ; Joseph & Hunter, ; Sanchez, Smith, & Adams, ), it reduced the negative effects of risk on youth adjustment (e.g., Schires et al, ), or it enhanced the positive effects of other promotive factors on youth adjustment (e.g., Tran & Lee, ).…”
Section: Associations Between Family Ethnic–racial Socialization and mentioning
confidence: 91%
“…Based on such existing, but limited, work, we expected that positive messages about one's ethnic background by way of cultural socialization would foster a strong sense of ethnic belonging and exploration. However, negative socialization messages, such as promotion of mistrust, would impede ethnic identity, perhaps by contributing to individuals feeling socially marginalized and alienated (Joseph & Hunter, ). In contrast, while preparation for bias might appear negative at the outset, such messages might be ultimately adaptive in communicating awareness of possible mistreatment and ways to cope with such realities (Hughes et al., ; Huynh & Fuligni, ).…”
Section: Interactive Processes In Identity and Youth Developmentmentioning
confidence: 99%